Countermeasures Against Cervical Cancer Through Detection of Fluor Albus Characteristic in Women at Medan, North Sumatera - Imelda, Fatwa; Nurbaiti (Talenta Publisher Universitas Sumatera Utara, 2018)
Cervical cancer is the first health problems for women in Indonesia with the highest risk of death. Delay diagnosis in late-stage cancer, vulnerable state, social status, low financial status, limited resource and facilities, type of histopathology and level of education determine patients’ prognosis. Fluor Albus is not a type of disease. It is a symptom of disease in female reproductive organs which can cause cervical cancer if it is not treated. Predisposition factors of Fluor Albus are including age, marital status, parity of menstrual cycle, contraception method, history of reproductive disorder, education, and job status. This community service aims to detect characteristic of fluor albus and to treat those identified with fluor albus atearly stage. The predisposition characteristics of fluor albus were collected from anamnesis while the Fluor Albus characteristic data were collected through direct observation of portio state of the uterian cervix. The activity was conducted from July to August 2017 in 3 different areas in Medan, North Sumatra with a total of 40 samples of women in their fertile age. Based on the analysis, 15 respondents (37.5%) found to suffer from Fluor Albus. Every woman is expected to be able to have early detection of Fluor Albus or symptoms of inflammatory infection of reproductive organs in order to prevent complication caused by Fluor Albus by paying more attention to personal hygiene, early screening by Pap Smear, IVA, and IHC (Immunohistochemistry).